(untitled) (Boston, 2011)
Higher Ambition is required reading for every leader who refuses to compromise between people and performance. Choosing one or the other may have worked in the past, but it won’t work now. As global competition stiffens and businesses face increased public scrutiny and renewed government regulation, leaders must win on all fronts—with their people, their customers, their communities, and their shareholders. In short, they must deliver superior economic and social value.
Keywords: Lãnh đạo,Leadership,Strategic planning,Success in business,Lập kế hoạch chiến lược,Thành công trong kinh doanh